2011
DOI: 10.1021/mp2000814
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA Condensation and Release by Lysine and Arginine Homopeptides Govern Their DNA Delivery Efficiencies

Abstract: Designing of nanocarriers that can efficiently deliver therapeutic DNA payload and allow its smooth intracellular release for transgene expression is still a major constraint. The optimization of DNA nanocarriers requires thorough understanding of the chemical and structural characteristics of the vector-nucleic acid complexes and its correlation with the cellular entry, intracellular state and transfection efficiency. L-lysine and L-arginine based cationic peptides alone or in conjugation with other vectors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
76
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 42 publications
(70 reference statements)
5
76
1
Order By: Relevance
“…Short peptides containing only arginine have the ability to translocate through cell membranes. 1, 9, 24, 2933 Furthermore, polymers or CPPs with some of their residues altered with arginine or the guanidine group displayed highly enhanced transfection efficiency. 32, 34 …”
Section: Introductionmentioning
confidence: 99%
“…Short peptides containing only arginine have the ability to translocate through cell membranes. 1, 9, 24, 2933 Furthermore, polymers or CPPs with some of their residues altered with arginine or the guanidine group displayed highly enhanced transfection efficiency. 32, 34 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 In particular, its ability to condense DNA with the positive charge and control DNA release make it possible to use polyarginine as an intracellular delivery vector for plasmid DNA (pDNA). 9 In addition, histidine has a proton sponge effect, thus making it possible to enhance the endosomal escape rate by increasing the pH of the endosomes, leading to osmotic swelling and bursting. 10,11 It was reported that stearylation could improve intracellular uptake and endosomal escape.…”
Section: Introductionmentioning
confidence: 99%
“…6, 14, 15 Thus, to facilitate polyanion-induced decomplexation of polyplexes especially in intracellular environments, degradable polymers responding to acidic pHs in the endolysosomes 16 or glutathione in the cytoplasm and the nucleus 14, 17, 18 have been developed. These polyplexes resulted in improved transfection efficiency.…”
Section: Introductionmentioning
confidence: 99%